A Survey on Tube Surfaces in Galilean 3-Space - Almaz, Fatma; Kulahci, Mihriban Alyamac (Gazi Univ, 2022)
In this study, the tube surfaces generated by the curve defined in Galilean 3-space are examined and some certain results of describing the geodesics on the surfaces are also given. Furthermore, the conditions of being geodesic on the tubular surface are obtained with the help of Clairaut's theorem, which allows us to constitute the specific energy. The physical meaning of the specific energy and the angular momentum is of course related with the physical meaning itself. Our results show that the specific energy and the angular momentum obtained on tubular surfaces can be expressed using arbitrary geodesic curve in Galilean space. In addition, some characterizations are given for these surfaces, with the obtained mean and Gaussian curvatures.
Keywords: Galilean space; tube surface; geodesic curve; specific kinetic energy; specific angular momentum